O uso do diário na pesquisa etnográfica da sala de aula de português como L2 (Cadernos de Linguagem e Sociedade, 2010)
A diary is a communicative situation in which the written word has a role; it is a literacy event. According to Barton (1994), literacy practices are the general ways of utilising literacy which people draw upon in a literacy event. Since 1992, diaries have been consistently used by student-teachers involved in language courses of the Programme of Research and Teaching in Portuguese for Speakersof Other Languages in the University of Brasilia. I examined some of these diaries written between 1990 and 1997 in order to show the different literacy practices which they draw upon.